Why is patent production so comparatively low at Petrobras? - Gay, Christopher Edward (2014)
As a latecomer firm, Petrobras’ innovation progress has previously been measured in terms of its productive capacity, capability accumulation, and more recently in terms of its strategic R&D and new product development. Patents are an acceptable proxy for innovation, especially for complex innovations such as biofuels and deepwater oil exploration & production, and this study evaluates Petrobras’ patent intensity relative to Shell and ExxonMobil for the years 2008–2012. The study found that while Petrobras may be a world-leader in deepwater E&P, its patent activities and portfolio are not competitive with its peers. This low patent intensity (and, by proxy, innovation) of Petrobras’ is explained by past and present institutional, cultural, and firm-specific factors.